Influence of different parameters on shear strength of FRP reinforced concrete beams without web reinforcement - Alam, Md. Shah (2010)
Thesis (Ph.D.)--Memorial University of Newfoundland, 2010. Engineering and Applied Science Bibliography: leaves 208-218. This research focuses on the shear behaviour of FRP reinforced concrete members without web reinforcement. The investigation was carried out in three phases, viz., experimental, analytical, and numerical simulation. The experimental investigation was carried out to investigate the effect of different parameters on the behaviour and concrete contribution to the shear strength. A new test set-up was designed and constructed for testing the beams. A total of thirty-six beams reinforced with GFRP, CFRP, and steel bars were tested. The test parameters were shear span-to-depth ratio (a/d), depth of beam (d), longitudinal reinforcement ratio (p), concrete compressive strength (f'c), and reinforcement type. Each of the parameters was varied while keeping all other parameters constant. The structural behaviour of the tested beams with regard to the deflections, strains, modes of failure, and ultimate capacity was examined. The test results revealed that there is an effect of the parameters on the shear strength of the beams. -- The experimental results were compared to the predictions of some of the available design codes, manuals, and guidelines for calculating the concrete contribution to the shear strength. It was observed that the predicted results did not match well with some of the experimental results. The experimental investigation revealed that there is a relationship between the cracking load and the shear strength of the beams. This relationship was further verified using the test results of 101 FRP reinforced beams that were available in the literature. Based on this relationship, a simple yet robust shear design method was proposed to calculate the concrete contribution to the shear strength of FRP reinforced rectangular beams without transverse reinforcement. The proposed method was validated against the experimental results of the current investigation as well the test results obtained from the literature. The predicted results using the proposed method were compared with the predicted results of some of the available design codes, manuals, and guidelines. The proposed method was found to be more consistent and reliable in predicting the shear strength of FRP reinforced concrete members than the other methods. The method is simple to apply and is suitable for use in design codes. -- Finally, finite element analysis was carried out to simulate the behaviour of shear critical FRP reinforced concrete beams with a wide range of design parameters such as shear span-to-depth ratio, depth of beam, reinforcement ratio, concrete strength, and reinforcement type. For this purpose, two concrete material models were used. The models were a concrete damage plasticity model (Model-1) and a hypoelastic concrete model (Model-2). An idealized tension-stiffening model was proposed based on the reinforcement type and varies as a function of the member strain. The models were implemented in general purpose finite element programs ABAQUS and ADINA, respectively. The models were used to simulate the experimental results of some of the beams tested in this investigation and to examine how well these models simulate the behaviour of shear critical FRP reinforced concrete members. The models predicted results are in a reasonable agreement with the experimental results. It was observed that a better prediction can be achieved using a proper tension-stiffening idealization.